The use of social networks sites (SNSs) among university students: how far do they learn - Syed Hassan, Sharifah Sariah; Landani, Zahra Mardani (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
The study investigated the pedagogical affordances of SNS and its relationship on student engagement. A sample of 300 students responded to this quantitative research using a self constructed questionnaire. The hypothesized model has been tested to determine the relationships between pedagogical affordances and student engagement. This model underpins the theory of constructivist of interactions that promote learning; connectivity and collaboration through Web 2.0 technology. Using Multiple Regression Analysis, the model is able to explain the significant relationships of connectivity, assessment and feedback and collaboration in predicting student engagement when learning via SNS. The implications of the study are discussed based on theory, practical importance and methodology of research.